Industrial Type UV-C Supported Portable Air Cleaning Unit - Yiğitcan Tokcan; İzzet Demir; Ahmet Uyumaz (Engineering Perspective)
In this study, it was made a portable air purification unit with UV-C supported. UV-C supported air purification nit was designed and produced that cleans and disinfects the air in closed communal living spaces such as hospital shopping malls, restaurants, industrial shops and offices. In the air cleaning unit; suitable components have been selected in the design and supplied. Assembly was performed in a wooden cabinet in a way that would work with UV support. The air is sent back to the environment by ozonizing the air with the ozone generator by passing through the UV-C fluorescent inside the PVC. As a general practice, the air-cleaning unit should be designed in accordance with ISO standards. It is seen that the designed and manufactured air cleaning unit has an impact volume of approximately 60 m3. Room class, total air change and maximum and minimum air flow were determined. The most important advantages of the system are its portability, light weight and silent operation. It can be also said that with its deodorizing feature, it eliminates the bad odor in the environment and givesit to the outside by means of the fan.